Acute influence of caffeinated commercially available energy drinks on performance, perceived exertion and blood lactate in youth female water polo players: Energy drinks on performance of water polo players - Arazi, Hamid; Rakhshanfar , Sara; Eghbali , Ehsan; Suzuki , Katsuhiko (Progress in Nutrition, 2021)
The purpose of this study was to investigate the effects of a commercially available energy drink (ED) on performance indicators, rating of perceived exertion (RPE) and blood lactate in youth female water polo players. Sixteen young Water Polo players (players in the league and national competitions) volunteered to participate in a double-blind repeated-measures crossover counterbalanced research. They ingested 6 ml/kg body weight of Red Bull (RB) or a placebo (PL) with the same appearance and taste. Fifteen minutes after ingestion, they performed following tests: strength or one repetition maximum (1RM) and 60% of 1RM in the chest press and leg press, 50 m and 100 m swimming test, running-based anaerobic sprint test (RAST) and aerobic test. Also, before and after aerobic test and RAST, 5 ml blood from antecubital vein was taken from participants to measure plasma lactate. In addition, participants’ RPE scales (15-point scale ranging from six (extremely light) to twenty (extremely hard)) were filled out before and after the aerobic and anaerobic tests. In comparison to the PL, the ingestion of ED reduces 50 m and 100 m swim record (Δ-change=-5.34, Δ-change=-5.85, P˂0.001; respectively) and increased aerobic (Δ-change=2.55, P˂0.001) and anaerobic performance (peak power: Δ-change=21.68, P=0.02; average power: Δ-change=24.04, P=0.03; fatigue index: Δ-change=0.98, P=0.003). The ingestion of the ED did not increase the muscular endurance in the bench press and leg press tests (P=0.59, P=0.35; respectively); Also, no differences were found in bench press strength between the two drink conditions (P=0.30). On the contrary, significance differences were found in leg press strength (Δ-change=2.56, P=0.03) and RPE post aerobic and anaerobic test between ED and PL (Δ-change=-0.72, P=0.04; Δ-change=-0.25, P=0.02; respectively). In contrast, blood lactate levels during the post exercise were unaffected by the ED ingestion (P=0.56, P=0.12; respectively). The intake of an ED (6 ml/kg body weight) increased some performance indicators and positively affected swimming at maximal speed. It seems that Red Bull ingestion may have a positive effect on water polo athletes’ performance due to significant impact on their aerobic and anaerobic metabolism.